Modernization of Islamic Boarding Schools in the Perspective of Azyumardi Azra: Modernisasi Pendidikan Pesantren dalam Perspektif Azyumardi Azra - Nur M, Kusuma Dwi; Ngainin, Nurul (Madrosatuna: Journal of Islamic Elementary School, 2021)
Pesantren is an Islamic educational institution with advantages in terms of its scientific tradition and the transmission and intensity of Muslims. The swift current of globalization has threatened the existence of Islamic boarding schools. The idea of ​​modernization emerged within the pesantren environment to answer the challenges of social transformation needs. However, many people are worried about the idea of ​​modernizing pesantren, which is oriented to the present. It can affect the identity and primary function of pesantren. This research focuses on the Problems and Efforts to Reform Institutional, Curriculum, and Islamic Boarding School Methodologies from Azyumardi Azra's Perspective. The purpose of this study is to find out the Problems and Efforts to Reform Institutional, Curriculum, Islamic Boarding School Methodology from Azyumardi Azra's perspective. The result of this research is that the modernization of pesantren in institutions such as agriculture, fisheries, or public schools within the pesantren environment has led to a decline in the identity of pesantren as educational institutions for Tafaqquh fi Al-Din and producing ulama'. The idea of ​​orienting pesantren to the "current" curriculum needs to be revisited because this idea may hurt the existence of the main tasks of the pesantren. Islamic boarding schools should be oriented towards improving the quality of their students towards the mastery of Islamic religious sciences. The use of strict and rigid methodologies in the curriculum system that prioritizes cognitive knowledge alone, according to it, can result in the process of forming the character and personality of students being neglected. So the pesantren must maintain its methodology, namely towards the learning process, taklim, and takdib so that pesantren can shape santri to become pious Muslims.